Kepuasan Kerja Dipengaruhi Oleh Lingkungan Kerja, Beban Kerja Dan Kepemimpinan Pada PT. Liebherr Indonesia Perkasa Balikpapan - Triana Putri, Erika; Ariani, Misna; Arrywibowo, Imam (Jurnal GeoEkonomi, 2025)
The pupose of study was to detemine the efect of Work Environme, Work load, leadership on Employe Job Satifaction at PT Liebherr Indonesia Perkasa Balikpapan. type study use quntitative research. sampling techniq study was puposive sapling a sanple 40 employes workshop departemen at PT Liebher Indonesia Perkasa Balikpapan. mpling with a sample 31 employes at PT Liebherr Indonesia Perkasa Balikpapan. Method coletion is done ditributing questionaire. study use SmartPLS to procesing data. result study indicat tha work enviroment varible no partial efect on employe job satifaction PT Liebherr Indonesia Perkasa Balikpapan, work load varible has a partial efect on employee job satifaction PT Liebher Indonesia Perkasa Balikpapan, leadership varible has no partial efect on employee job satifaction PT Liebherr Indonesia Perkasa Balikpapan.